Anonymous

# if x-y=15 and 3x+y=13 then y=?

a. -8

b. -7

c. 7

d.8

### 4 Answers

Relevance

- lenpol7Lv 74 weeks ago
Simulttaneous equations.

Add ; this will eliminate 'y'

4x = 28

x = 7

When x = 7

7 - y = 15

y = 7 - 15

y = -8

Ans; 'a'

- PhilipLv 64 weeks ago
...x-y = 15...(1).;

3x+y = 13...(2),;

[(1)+(2)] ---> 4x = 28, ie., x = 7. Then (1) ---> y = x-15 = -8. a. shows correct answer.

- llafferLv 74 weeks ago
You have a system of two equations and two unknowns. We can solve this with substitution:

Since you want "y", we'll start with solving the first equation for "x" in terms of "y":

x - y = 15

x = 15 + y

Now substitute this expression in for "x" in the other equation, then solve for y:

3x + y = 13

3(15 + y) + y = 13

45 + 3y + y = 13

45 + 4y = 13

4y = -32

y = -8

Answer "A".

Still have questions? Get answers by asking now.